Fracturing parameter optimization technology for highly deviated wells in complex lithologic reservoirs - Hao, Lihua; Zhang, Binxin; Chen, Beibei; Wang, Hongwei; Wu, Yuankun; Pan, Liyan; Huang, Yue (Frontiers in Energy Research, 2023)
For complex lithologic reservoirs, highly deviated wells face difficulties in geomechanical transformation and how to optimize fracturing parameters. This paper is based on geological mechanics laboratory experiments and logging interpretation, combined with regional geological background, to clarify the geological and mechanical characteristics of the Fengcheng Formation shale oil region in the Mabei Slope. On this basis, based on the current geostress field and natural fracture distribution pattern of the Mabei Slope, an integrated model of shale oil geological engineering in local well areas was established.Based on the finite element method, optimization design was carried out for the cluster spacing, construction fluid volume, displacement, and sand volume of highly deviated well fracturing, and three-dimensional simulation of fracturing fractures was completed. The research results indicate that the current dominant direction of the maximum principal stress in the Fengcheng Formation on the Mabei Slope is from northeast to southwest, with the maximum horizontal principal stress generally ranging from 90 to 120 MPa and the minimum horizontal principal stress generally ranging from 70 to 110 MPa. The difference in stress between the two horizontal directions is relatively large, generally greater than 8 MPa. Two sets of natural fractures have developed in the research area, one with a northwest southeast trend and the other with a northeast southwest trend.The natural fracture density of the Fengcheng Formation shale reservoir in the Mabei Slope is 0.32-1.12/m, with an average of 0.58/m, indicating a moderate to high degree of fracture development. Second, the geological model and three-dimensional geo-mechanical model are established according to the actual drilling geological data, and different schemes are designed to carry out single parameter optimization. The optimization results show that the optimal cluster spacing of the subdividing cutting volume pressure of the highly deviated wells in the Fengcheng Formation of the Mabei Slope is 12 m, the optimal construction fluid volume is 1400-1600 m 3 /section, the optimal construction displacement is 8 m 3 /min, and the optimal sanding strength is 2.5 m 3 /m. This research has been well applied in Mahu area of Xinjiang oilfield.